THE ESSENCE OF ECONOMIC ANALYSIS AND ITS ROLE IN A CONSTRUCTION COMPANY MANAGEMENT - Oleksandra Kononova; Tetiana Ivanytska (Izdevnieciba "Baltija Publishing", 2017)
The analysis is a method of scientific investigation of phenomena and processes (in the case under consideration, the economic activity of a construction enterprise), which is based on the study of the component parts of the system under study in order to identify its characteristics and development trends. The main goal of analysis is to assess the current state of the economic management object and identify trends that determine its further development.